2021
DOI: 10.21601/ijese/10962
|View full text |Cite
|
Sign up to set email alerts
|

STEAM Education Using Sericulture <i>Ukiyo-e</i>: Object-Based Learning through Original Artworks Collected at a Science University Museum in Japan

Abstract: Societies across the world face the need to increase the number of science, technology, engineering, and mathematics (STEM) personnel who could resolve issues concerning sustainability. The body of scholarly literature on STEM education has grown significantly since the beginning of the 21st century. STEAM education incorporates arts with STEM subjects. This pedagogical strategy is increasingly adopted in formal/informal education settings to foster scientific thinking and creativity through multisensory artis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This feature means that STEAM education is not a separate discipline, but an integration of multiple disciplines, including science, engineering, technology, art, and mathematics. In the education process, a subject education integrates the knowledge of other subjects throughout the education, so that students can master the comprehensive application of multiple subjects to cultivate students’ ability to integrate multiple subjects for innovation and interdisciplinary thinking ( Tanabashi, 2021 ). The situational nature of STEAM education is a more important feature.…”
Section: Research Theories and Methodsmentioning
confidence: 99%
“…This feature means that STEAM education is not a separate discipline, but an integration of multiple disciplines, including science, engineering, technology, art, and mathematics. In the education process, a subject education integrates the knowledge of other subjects throughout the education, so that students can master the comprehensive application of multiple subjects to cultivate students’ ability to integrate multiple subjects for innovation and interdisciplinary thinking ( Tanabashi, 2021 ). The situational nature of STEAM education is a more important feature.…”
Section: Research Theories and Methodsmentioning
confidence: 99%
“…At the core of the OBL perspective lies the idea that objects can serve as effective learning tools. The pedagogical approach of OBL involves the in-depth, multisensory exploration of tangible objects to enhance students' engagement and cultivate profound and meaningful learning experiences [10]. Objects are harnessed in various ways to foster both discipline-specific knowledge and transferable skills, such as communication, teamwork, practical observation, and drawing skills.…”
Section: Object-based Learning and Scientific Instrumentsmentioning
confidence: 99%
“…Mora et al [18] observed that some frameworks consider using technology as a prerequisite for gamification, while some researchers support that "[g]amification can also be done completely offline by adding motivational narratives as a prequel to an activity or by awarding paper badges or medals for certain educational achievements" [1] (p. 456). In this sense, gamification could be associated with object-based learning (OBL) [29], wherein manipulative materials play a pedagogical role. Most frameworks of gamification address fun as a relevant aspect to be considered during the design process of gamification.…”
Section: Introductionmentioning
confidence: 99%